2022
DOI: 10.1111/1759-7714.14361
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic intrathoracic chemotherapy for the treatment of malignant pleural effusion caused by breast and ovarian cancer: A systematic literature review and pooled analysis

Abstract: Breast and ovarian cancer account for over 30% of malignant pleural effusions (MPEs). Treatment of the metastatic disease requires control of the MPE. Even though primarily symptomatic, the treatment of the MPE can potentially affect the oncological course of the disease. The aim of this review is to analyze the effectiveness of intrathoracic chemotherapy in the treatment of MPE caused by breast and ovarian cancer. Methods: A systematic literature research was conducted up until May 2021. Studies published in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…showed a promising survival in patients with ovarian cancer with pleural metastases after combined abdominal and thoracic CRS ( 27 ). The use of HITOC without CRS showed to be helpful for relieving the symptoms of pleural effusion in patients with metastatic ovarian cancer ( 28 ). Nikiforchin et al.…”
Section: Discussionmentioning
confidence: 99%
“…showed a promising survival in patients with ovarian cancer with pleural metastases after combined abdominal and thoracic CRS ( 27 ). The use of HITOC without CRS showed to be helpful for relieving the symptoms of pleural effusion in patients with metastatic ovarian cancer ( 28 ). Nikiforchin et al.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis assessed the role of intrathoracic chemotherapy for control of malignant pleural effusion secondary to breast cancer and ovarian cancer and demonstrated that it achieves symptomatic control in 59% of metastatic breast and 87% of metastatic ovarian cancer patients and was inferior to other forms of pleurodesis, especially surgical pleurodesis. 30 Thus, routine use of intrapleural chemotherapy for extrathoracic metastatic disease to the pleura is limited.…”
Section: Intrapleural Anticancer Therapy For Malignant Pleural Diseasesmentioning
confidence: 99%
“…Finally, a recent systematic literature review and pooled analysis by Karampinis et al demonstrated success in the use of intrathoracic chemotherapy. In their study they demonstrated that in patients with breast or ovarian cancer, intrathoracic chemotherapy was successful in reducing MPE in 59.1% and 87.5% of patients, respectively [ 57 ]. Multiple other chemical pleurodesis agents and indwelling catheters are currently in various stages of assessment at this time.…”
Section: Future Directionsmentioning
confidence: 99%